Gut Microbiome Alterations in Patients With Thyroid Nodules - Li, Ang; Li, Tiantian; Gao, Xinxin; Yan, Hang; Chen, Jingfeng; Huang, Meng; Wang, Lin; Yin, Detao; Li, Hongqiang; Ma, Runsheng; Zeng, Qiang; Ding, Suying (Frontiers in Cellular and Infection Microbiology, 2021)
Thyroid nodules are found in nearly half of the adult population. Accumulating evidence suggests that the gut microbiota plays an important role in thyroid metabolism, yet the association between gut microbiota capacity, thyroid nodules and thyroid function has not been studied comprehensively. We performed a gut microbiome genome-wide association study in 196 patients with thyroid nodules and 283 controls by using whole-genome shotgun sequencing. We found that participants with high-grade thyroid nodules have decreased number of gut microbial species and gene families compared with those with lower grade nodules and controls. There are also significant alterations in the overall microbial composition in participants with high-grade thyroid nodules. The gut microbiome in participants with high-grade thyroid nodules is characterized by greater amino acid degradation and lower butyrate production. The relative abundances of multiple butyrate producing microbes are reduced in patients with high-grade thyroid nodules and the relative abundances of L-histidine metabolism pathways are associated with thyrotropin-releasing hormone. Our study describes the gut microbiome characteristics in thyroid nodules and a gut-thyroid link and highlight specific gut microbiota as a potential therapeutic target to regulate thyroid metabolism.